The Difference of Mesiodistal Tooth Size Ratio Using Bolton Analysis for Palembang and Toba Batak Ethnicities - Vida Irena Phelia; Arya Prasetya Beumaputra; Indri Seta Septadina (Sriwijaya Journal of Dentistry, 2020)
Introduction. Bolton's analysis is often used to determine discrepancy in tooth size. Mesiodistal size of teeth in each race & ethnicity is different, resulting in a different ratio of mesiodistal teeth size. The mesiodistal tooth size ratio is very important in determining the orthodontic treatment plan so that a good occlusion can be achieved as the end result of treatment. The purpose of this study was to determine the difference in the ratio of mesiodistal teeth size between Palembang and Batak Toba ethnic according to Bolton's analysis.Methods. This is a cross-sectional analytic study. The number of participants was 60 subjects divided into 2 groups, Palembang and Batak Toba ethnicity (n=30). All samples consisting of the maxilla and mandible study cast from each participant then were measured the mesiodistal size ratio of the teeth using Bolton's analysis with Sliding Caliper. The data were analyzed using an independent T-test. Results. The results of this study indicate that there is no significant difference between the ratio of mesiodistal tooth size according to Bolton's analysis of the ethnic Palembang and Batak Toba both in the anterior ratio and the overall ratio. Only the anterior ratio of the Toba Batak ethnic group has a significant difference with the Bolton anterior ratio.Conclusion. The Bolton overall ratio (91.3) can be used for the Palembang and Toba Batak ethnic groups in Palembang, while the Bolton anterior ratio (77.2) can only be used for the Palembang ethnic group and cannot be used for the Toba Batak ethnic group in Palembang.